ANALISIS KAUSALITAS PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH DAN KUALITAS SUMBERDAYA MANUSIA DI PROVINSI SUMATERA BARAT - Hanifa Novela; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the causal relationship between economic growth, government expenditure and the quality of human resources in West Sumatra. This type of research is descriptive and associative research, where the data used is secondary data in the form of panel data from 2010 to 2017 with the technique of collecting documentation data and literature study obtained from related institutions and institutions. The data analysis used is the data used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: (1) Unit Root Test (2)Cointegration Test (3) Optimal Lag Determination (4) Granger Causality Test (5) PVAR Test. The results of this study indicate that (1) economic growth and government expenditure have a one-way relationship where economic growth affects government spending while government spending does not affect economic growth (2) economic growth and quality of resources humans have a one-way relationship where economic growth affects the quality of human resources and the quality of human resources does not affect economic growth (3) government expenditure and the quality of human resources do not have one-way or two-way relationships ( causality) where government spending does not affect the quality of human resources as well as the quality of human resources does not affect government spending during the study period